Meaningful Information The Bridge Between Biology, Brain, and Behavior - Reading, Anthony; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
The book introduces a radically new way of thinking about information and the important role it plays in living systems. It opens up new avenues for exploring how cells and organisms change and adapt, since the ability to detect and respond to meaningful information is the key that enables them to receive their genetic heritage, regulate their internal milieu, and respond to changes in their environment. It also provides a way of resolving Descartes$1 (Bdilemma by explaining the workings of the brain in non-mechanical terms that are not tainted by spiritual or metaphysical beliefs. The types of meaningful information that different species and different cell types are able to detect are finely matched to the ecosystem in which they live, for natural selection has shaped what they need to know to function effectively in those circumstances. Biological detection and response systems range from the chemical configurations that govern genes and cell life to the relatively simple tropisms that guide single-cell organisms, the rudimentary nervous systems of invertebrates, and the complex neuronal structures of mammals and primates. The scope of meaningful information that can be detected and responded to reaches its peak in our own species, as exemplified by our special abilities in language, cognition, emotion, and consciousness, all of which are explored within this new framework.s
1.Introduction -- 2. Meaningful Information -- 3. Cause and Effect -- The Detection of Form -- 5. The Doorways of Perception -- 6. Response Systems -- 7. Cognitive Processing -- 8. Storage and Retrieval -- 9. Knowledge and Understanding -- 10. Communication -- 11. Language -- 12. Cellular Signals -- 13. Genetic Messages -- 14. Feelings as Information -- 15. Consciousness -- 16. Maladaptive Behavior -- 17. Fabricated Devices.
Keywords: Life sciences; Neurosciences; Science -- Philosophy; Evolution (Biology).; Consciousness; Life Sciences; Evolutionary Biology; Cognitive Psychology; Philosophy of Science; Neurosciences